2020
DOI: 10.1016/s2468-2667(20)30052-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol use and drinking patterns in socioeconomic inequalities in mortality: a systematic review

Abstract: Background Individuals with low socioeconomic status (SES) experience disproportionately greater alcohol-attributable health harm than individuals with high SES from similar or lower amounts of alcohol consumption. Our aim was to provide an update of the current evidence for the role of alcohol use and drinking patterns in socioeconomic inequalities in mortality, as well as the effect modification or interaction effects between SES and alcohol use, as two potential explanations of this so-called alcohol-harm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
168
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 39 publications
18
168
0
1
Order By: Relevance
“…Piazza et al reported that alcohol consumers were more physically active than non-drinking peers; moreover, the authors concluded that these findings were contrary to the hypothesis of the investigators [ 47 ]. Despite this, it has been demonstrated that excessive alcohol consumption is associated with an increased risk of mortality [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piazza et al reported that alcohol consumers were more physically active than non-drinking peers; moreover, the authors concluded that these findings were contrary to the hypothesis of the investigators [ 47 ]. Despite this, it has been demonstrated that excessive alcohol consumption is associated with an increased risk of mortality [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education, employment, and income are the most frequently pointed out determinants related to socio-economic status (SES) that can influence both patterns of alcohol consumption and their health-related harm. This has been confirmed by the literature reviews, which indicate complex, multifaceted relationships between social determinants, inequities, and alcohol consumption [5,6], on one hand, and the role of alcohol use and drinking patterns in socio-economic inequalities in mortality, on the other hand [1,[7][8][9]. However, individuals with a higher SES may consume similar or greater amounts of alcohol compared to those with a lower SES.…”
Section: Introductionmentioning
confidence: 74%
“…Alcohol use is recognized as an important determinant of health. Reducing alcohol drinking might aid in achieving some of the 17 Sustainable Development Goals (SDG) adopted by all United Nations Member States in 2015, including those focusing on maternal and child health, non-communicable diseases (NCD), infectious diseases as well as mental health, injuries, and poisonings [1][2][3][4]. Alcohol consumption is also shown as one of the indicators for the SDG health target 3.5-"Strengthen the prevention and treatment of substance abuse, including narcotic drug abuse and harmful use of alcohol" [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study offers many implications for the policies' creators. Probst et al were ambitious in researching different alcohol consumption impacts on health among individuals with a low/high socioeconomic status [20]. Authors confirm a relation between alcohol consumption and socioeconomic status, even though the process in general is complex.…”
Section: Introductionmentioning
confidence: 99%